Peluang pengajaran BIPA di tingkat pendidikan tinggi di Timor Leste - Sri Rejeki; Choirul Asari (BAHASTRA, 2019)
The aim of this article is to describe about the chance to teach Indonesian language as a foreign language in higher institutions in Timor Leste and the motivation of the students in learning Indonesian language. Timor Leste people use Indonesian language as a working language and as a teaching language in some educational institution. This study is a descriptive qualitative research and uses questionnaire to gather the data. The respondent of this study are 11 Timorese students who study in higher education. The data shows that not all universities have Indonesian language course but they use Indonesian language as a teaching language in their institutions. On contrary, almost all senior high school in Timor Leste have Indonesian language course in their curriculum. The position of Indonesian language in Timor Leste als influences the motivation of the students to learn Indonesian language. Suggestions for further research and related institutions are provided.